ANALISIS JEDA WAKTU TERJADINYA SERANGAN ATAU ANCAMAN TERHADAP PEMBELAAN TERPAKSA - Shalahudin - Serbabagus; Adam Wildan Mubarak (Universitas Islam Darul Ulum, 2022)
KUHP does not only regulate non-prohibited rules that are criminal in nature or violations. but also fully regulates legal protection. as is the case in limited or noodweer cleavage. The limited defense itself is still divided into an extraordinary limited defense or noodweer excess. The problem is that there is a time lag that needs to be explained further because in general the time lag is only said to be instantaneous when a threat or attack occurs. and the lack of explanation of the instantaneous word itself. The approach used in this research is the statutory approach and the conceptual approach, the case approach of this normative research. With such a methodological approach, the time lag for the forced defense can be explained in detail. Keywords : KUHP; Limited Defense; Noodweer; Noodweer excess